Giant dielectric constant materials and their applications - Varela, José A. [UNESP]; Orlandi, Marcelo O. [UNESP]; Ramirez, Miguel A. [UNESP]; Foschini, Cesar R. [UNESP]; Felix, Anderson A. [UNESP] (Springer Nature, 2012)
There is a constant need in the modern electronic industry for capacitors with high capacity per volume in order to use in many applications such as memories devices, energy storage, microwave filters, among others. The synthesis, characterization and study of materials with a very high or giant dielectric constant are in particular important and have been studied by many investigators. Then the search for high dielectric materials has been driven, which must requires some special properties such as to keep dielectric constant almost independent of temperature and frequency and low dielectric loss. In recent years many material systems have been searched, including perovskite and others, aiming to achieve a reliable material for practical applications. In this chapter we review many classes of materials including titanates, nickeletes, cuprates, multiferroics and composites such as cermets, ceramic/polymer and ceramic/ceramic. To the end of this work is presented the most important models in the literature to explain mechanism for giant dielectric constant. The main task is to understand the mechanism that controls materials properties in order to synthesize an optimized material that maximizes those properties by using sol-gel or other chemical-like synthesis for many applications in the electronic industries.
Keywords: Capacitors; Ferroelectric; Giant dielectric materials; Multiferroics; Perovskite-based materials